Exclusão de sócio por falta grave na sociedade limitada bipessoal - Barros Neto, Geraldo Fonseca de (2019)
Adequating the legal rules on the exclusion of partner for the specificities of the two-partners partnership is the purpose of this thesis. In committing a serious misconduct, which jeopardizes business activity, the member disobeys his duties and is subject to exclusion from the partnership, even when the partners are only two. The exclusion of the defaulting partner is the effect of the partial resolution of the partnership agreement due to the default of one of its partners. The company, which is the addressee of the duties of the partners, is the holder of the right to exclude one of its members for serious misconduct. The party legitimized to propose the exclusion of a partner is, therefore, the society, even in the bipersonal society. If the representative of the company in court is the partner that is to be excluded, the judge must appoint the person in charge of the representation, who may be one of the partners or third party. The exclusion of a partner may take place out-of-court, targeting the minority partner, even in the bipersonal limited partnership, provided there is provision in the social contract and respect for legal procedure. The exclusion can also be operated judicially (or by arbitration), through the special procedure of partial dissolution, whose specialty, in fact, is minimal. Even if possible the out-of-court exclusion, the company has processual interest in in the judicial process, preferring the legally safe way. The legal prohibition is incompatible with the protection of legal certainty